Collaborative Approaches to the Management of Geospatial Data Collections in Canadian Academic Libraries: A Historical Case Study - Trimble, Leanne; Woods, Cheryl; Berish, Francine; Jakubek, Daniel; Simpkin, Sarah (Université d'Ottawa | University of Ottawa, 2015)
The Ontario Council of University Libraries (OCUL) is a consortium of the twenty-one university libraries in Ontario, Canada. Since 1967, OCUL member institutions have worked together to share costs and workload through collective purchasing and licensing of information resources and more recently through the establishment of a shared digital infrastructure known as Scholars Portal. Under the auspices of OCUL, Ontario’s university map librarians formed the OCUL Map Group in 1973 to seek opportunities to communicate and collaborate to improve the collections and services they offer their users. The opportunities provided by collaboration have ensured a greater capacity to manage evolving collections of geospatial data. The group has served as a community of practice, which has provided educational opportunities and facilitated collaborative problem solving through a listserv, conference calls, and face-to-face meetings. This collegial environment has also led to the completion of a number of projects, which have resulted in the creation of new technical infrastructures and strategies for sharing the workload of data management tasks. This paper discusses the role of collaboration in OCUL projects and offers some suggestions for others considering embarking on collaborations of their own
Keywords: GIS libraries; library consortia; collaboration; map collections; geospatial data collections; geospatial data portals; map digitization